Rhinoplasty Using Autologous Costal Cartilage - Miranda, Nancy; Larocca, Carlos Gil; Aponte, Ciro (Facial Plastic Surgery, 2013)
Most Latin American patients looking to have a primary septorhinoplasty share common characteristics in relation to an incorrect projection of the nasal tip complex and a low dorsal line. Thus, the frequent use of structural techniques and of surgical enhancement techniques becomes necessary to improve the nasal contour. In cases of secondary septorhinoplasty, it is also usual in our practice not to have sufficient septal cartilage available or with the required quality to give structure and support to the nasal tip complex, handle the nasal dorsum, and simultaneously correct postseptorhinoplasty deformities. For these reasons, in our practice costal cartilage represents an excellent option as autologous graft material. We present our experience using autologous costal cartilage for structural and nonstructural purposes in 286 selected patients who underwent open rhinoplasty between 2004 and 2011. We emphasize preoperative analyses, we discuss the criteria for selecting costal graft as graft material, we show key aspects of the dynamic of the surgery, and we consider the possibility of using autologous costal graft in combination with heterologous grafts. In this work we also establish the disadvantages of costal cartilage as graft material in specific areas of the surgical anatomy of the nose.
Keywords: septorhinoplasty; mestizo nose; costal cartilage